(untitled) (International Journal of Ayurveda and Pharma Research, 2023)
Therapeutics in Ayurveda is really a treasure to be explored, understand and utilized to its maximum benefit. The preparations in Ayurveda are a reflection of its personalized medicine theory. Each formulation is designed and modified in such a way that it can suit to a person’s condition in every aspect. Ayah paatra pralepanam is one of the unique therapeutic methods in this science. Most of the preparations in this method is ideal for curing the hepatic pathologies. In this paper an attempt is to done to explain the preparation of one among the valued herbo mineral preparation named Yogaraja Choornam. The preparation of the formulation involves the identification of genuine raw materials, powdering the herbal drugs to a fine size, for mineral drugs it involves its purification, incineration, finally proper mixing and the smearing of formulation in an iron vessel. Standardization of Ayurvedic formulation is an on-going process where one needs to be keen in identifying the new scientific methods to study the fine chemical procedures and the intermediate compounds formed, but at the same time be vigilant in sticking to the classical in parameters to be followed. For the mineral drugs the Bhasmas produced are subjected to classical evaluation like Sookshmatvam (fineness), Rekhapurnada, Vaaritaratvam, Uthan/unamam, Niswadu etc to confirm the Ayurvedic standards of Bhasmas. They are also subjected for XRD, XRF, SEM and AAS estimation for identifying the crystal structure, elemental analysis and fineness and composition. For the Ayaah pralipta Yogaraja Choornam the pH, ash values, particle size estimation, loss on drying, water extractives values and microbial load estimation are done. The values affix the standard for the formulation. Standardization of Yogaraja choorna is done which creates a background for the further studies to be carried out on the formulation.